Uji Coba Metode Critical Insident pada Evaluasi Kinerja Karyawan PT. Nikomas Gemilang Divisi Nike - Yulanda Puspita Reni; Putri Nada Sari; Syamsul Hidayat (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to test employee performance evaluation at PT. Nikomas Gemilang, Nike Division, using the Critical Incident Technique (CIT) method. This method was chosen to explore critical incidents that affect employee performance, both positively and negatively, within the context of their work. This study used a qualitative approach with data collection techniques in the form of in-depth interviews with employees from various departments, such as Chemical Quality Control, Outsole Operators, Line Supervisors, the Chemical QC Department, and Admin. The results showed that positive incidents involving promotions and training contributed to improved performance, while negative incidents were more related to operational challenges that required improvement through training. This study provides insight into the importance of critical incident management in employee performance evaluation and provides recommendations for improving the training and promotion system at PT. Nikomas Gemilang.